Effect of He's Santong Needling Method on Dysphagia after Stroke: A Study Protocol for a Prospective Randomized Controlled Pilot Trial. (14th August 2018) - Zhao, Luopeng; Liu, Lu; Zhang, Claire Shuiqing; Zeng, Lin; Zhao, Jingxia; Wang, Linpeng; Jing, Xianghong; Wang, Kelun; Li, Bin
Abstract : Background . Dysphagia is a common complication of stroke, affecting up to 78% of stroke patients. The existence of dysphagia after stroke has been associated with an increased risk for pulmonary complications and even mortality. Previous studies have shown that acupuncture could be potential therapeutic method for treatment of dysphagia after stroke. A prospective randomized controlled pilot trial is designed to evaluate the effect of He's Santong needling method on dysphagia after stroke. Methods and Design . Sixty eligible participants will be recruited and randomly assigned into treatment group (He's Santong needling method and swallowing rehabilitation training) and control group (swallowing rehabilitation training) in a 1:1 ratio. All treatments will be provided everyday on weekdays with a two-day interval at the weekend, during a total treatment course of four weeks. The Penetration-Aspiration Scale with Fiberoptic Endoscopic Examination of Swallowing will be assessed at baseline and endpoint (Week 4) as primary outcomes. The Saitoh's classification score, Swallowing-Related Quality of Life score, the Modified Mann Assessment of Swallowing Ability score, and Surface Electromyography will be evaluated at baseline and endpoint as secondary outcomes. Ethics and Dissemination . The trial protocol has been approved by the Research Ethical Committee of Beijing Hospital of Traditional Chinese Medicine Affiliated to Capital Medical University on 9 May 2017 (ethical batch number: 2017BL-013-02). Each participant will be notified regarding the study protocol. Written informed consent will be obtained from each participant. Trial Registration . ISRCTN registry: ISRCTN68981054 ; Registered on 25 September 2017.